A retrospective cross-sectional study on the association between newborn’s head circumference at birth and obstetric anal sphincter injuries among primigravidae / Ng Jun Jiet ... [et al.] - Ng, Jun Jiet; Chan, Yan Ling; Ismail, Ahmad Amir; Apana, Aruku Naidu; Aruku Naidu, Thuvina (Faculty of Medicine, 2022)
Introduction: Obstetric anal sphincter injuries (OASIS) is a term used to describe third- and fourth- degree perineal trauma during childbirth. There are a lot of risk factors associated with OASIS, however newborn’s head circumference (HC) at birth as a risk factor is understudied. The aim of this study was to determine the incidence of OASIS and establish the association between newborn’s HC at birth and OASIS among primigravidae who delivered in Hospital Raja Permaisuri Bainun (HRPB) from 2016 to 2018. Other OASIS risk factors were also analysed. Methods: This was a retrospective cross-sectional study among primigravidae who delivered in HRPB from 2016 till 2018. Systematic sampling method was used, and the total sample recruited was 538. Women who sustained OASIS were compared to women without OASIS. Simple and multiple logistic regression analysis were used to look for the association between associated risk factors and OASIS. Results: The incidence of OASIS in HRPB during the study period was 2.0%. Newborn’s HC at birth (p=0.588) was not significantly associated with OASIS, whereas birth weight (OR 1.002 95%CI 1.001-1.004 p=0.06) and instrumental delivery (OR 8.13 95%CI 1.91-34.59 p=0.05) were significant risk factors for OASIS. Conclusion: Overall incidence of OASIS in HRPB was 2.0%, which is within the normal range. Newborn’s HC was not significantly associated with the occurrence of OASIS. Birth weight and instrumental delivery were significant risk factor for OASIS. This information can be used for patient counselling and shared decision making.